Bridging Trade Barriers: Evaluating Models of Multi-Product Exporters - Björn Thor Arnarson (Lund University, School of Economics and Management, Department of Economics, 2016)
In this paper I investigate the impact of a decrease in trade costs on firms' decisions to export. The main contribution of this paper is to evaluate empirically the theoretical predictions of several models of multi-product exporters. The focus is on the firm export entry decision and the within firm adjustment regarding product scope and intensity. For identification I use a quasi-natural experiment, the introduction of the Öresund Bridge between southern Sweden and Denmark, to analyse the impact on firm behaviour. Using a difference-in-difference methodology, firms in the 'treated' municipality, Malmö, are compared to firms in more geographically distant Gothenburg and Stockholm ('controls'). For the 'treated' manufacturing firms a theoretically consistent positive effect is found for firm entry into exporting, aggregate firm trade flow and the number of products exported. The models of multi-product exporters evaluated do not provide a clear theoretical prediction regarding the impact on average trade value per product. In this paper, however, I find that around 70-80% of the increase in aggregate firm trade value is due to increases in the average trade value per product (the product intensive margin), while only 20-30% is due to increases in the number of products exported (the product extensive margin).
Keywords: F10; F13; F14; F15; 330; International Trade; Multi-Product Firms; Infrastructure; Market Access; Quasi-Natural Experiment; Trade Costs